Increased Extravascular Lung Water Reduces the Efficacy of Alveolar Recruitment Maneuver in Acute Respiratory Distress Syndrome - Alexey A. Smetkin; Vsevolod V. Kuzkov; Eugeny V. Suborov; Lars J. Bjertnaes; Mikhail Y. Kirov (Critical Care Research and Practice)
Introduction. In acute respiratory distress syndrome (ARDS) the recruitment maneuver (RM) is used to reexpand atelectatic areas of the lungs aiming to improve arterial oxygenation. The goal of our paper was to evaluate the response to RM, as assessed by measurements of extravascular lung water index (EVLWI) in ARDS patients. Materials and Methods. Seventeen adult ARDS patients were enrolled into a prospective study. Patients received protective ventilation. The RM was performed by applying a continuous positive airway pressure of 40 cm H2O for 40 sec. The efficacy of the RM was assessed 5 min later. Patients were identified as responders if PaO2/FiO2 increased by >20% above the baseline. EVLWI was assessed by transpulmonary thermodilution before the RM, and patients were divided into groups of low EVLWI (<10 mL/kg) and high EVLWI (≥10 mL/kg). Results. EVLWI was increased in 12 patients. Following RM, PaO2/FiO2 increased by 33 (4–65) % in the patients with low EVLWI, whereas those in the high EVLWI group experienced a change by only −1((−13)–(+5)) % (𝑃=0.035). Conclusion. In ARDS, the response to a recruitment maneuver might be related to the severity of pulmonary edema. In patients with incresed EVLWI, the recruitment maneuver is less effective.